Physicochemical and Biological Analysis of 99mTc-Glutathione Radiopharmaceuticals - M.E. Sriyani; N. Zainuddin (Atom Indonesia, 2013)
99mTc-glutation (99mTc-GSH) radiopharmaceutical is available in the GSH lyophilized-kit in which ready to use directly after adding 99mTc radionuclide. In nuclear medicine, 99mTc-GSH diagnostic kit is a radiopharmaceutical commonly utilized for cancer diagnoses using imaging method. This paper described the physicochemical and biological characteristics as well as the quality of 99mTc-GSH diagnostic kit prepared from the GSH lyophilized-kit. The radiochemical purity was determined with thin layer chromatography (TLC) method, performed on a TLC-SG stationary phase with a mobile phase of a dried acetone and 0,9% of NaCl solution. Studies on the effect of volume and radioactivity of Na99mTcO4 solution to the radiochemical purity of 99mTc-GSH were carried out. The sterility of GSH-lyophilized kit and toxicity of 99mTc-GSH were also investigated. The stability test on GSH lyophilized kit and 99mTc-GSH in several storage conditions, as well as the plasma stability of 99mTc-GSH was performed. The analysis result showed that the GSH lyophilized-kit was sterile; the 99mTc-GSH was non toxic with 99.54 ± 0.01% of radiochemical purity and remained stable 5 hours either at room temperature or 4 oC. The volume more than 4 mL of Na99mTcO4 solution on the labeling of GSH could decreased the 99mTc-GSH radiochemical purity, while the radioactivity more than 20 mCi in 7 mL of volume extended the incubation time. In-vitro stability test of 99mTc-GSH in plasma showed that in the two hours of storage, the radiochemical purity decreased to 51.84 ± 2.52%, and until 5 hours of storage it did not change significantly. From the result, it can be concluded that the GSH lyophilized-kit was remained stable after 13 month of storage either at room temperature or at 4 oC with 99% of 99mTc-GSH radiochemical purity.Received: 16 January 2013; Revised: 23 August 2013; Accepted: 24 August 2013